Patch testing of budesonide in Italy: The SIDAPA baseline series experience, 2018–2019. (24th May 2021) - Stingeni, Luca; Marietti, Rossella; Bianchi, Leonardo; Guarneri, Fabrizio; Ferrucci, Silvia Mariel; Faraci, Andrea Giuseppe; Foti, Caterina; Romita, Paolo; Patruno, Cataldo; Napolitano, Maddalena; Gallo, Rosella; Corazza, Monica; et al.
Abstract: Background: Budesonide was included in the European Baseline Series in 2000 as the most suitable marker forcorticosteroid hypersensitivity. In the last two decades, a decreasing trend of budesonide allergy has been observed. Objectives: To estimate the prevalence of positive patch test reactions to budesonide in a large, Italian patch test population, characterizing patients according to MOAHLFA index and evaluating the benefit with extended readings of budesonide patch test. Methods: Retrospective analysis of patient demographics and patch test results over a 2‐year period (2018–2019) was performed at 14 patch test clinics in Italy. Results: Ninety out of 14 544 (0.6%) patients reacted to budesonide 0.01% pet.. Positive reactions were mild in 54.4% and late readings at day 7 showed new positive reactions in 37.8% of patients. The MOAHLFA index showed a significant positive association with male gender, atopic dermatitis, and age >40 years and a significant negative association with hand and face dermatitis. Conclusions: We documented a low prevalence of budesonide allergy in Italy, confirming its decreasing trend recently reported in the literature. Nevertheless, budesonide needs to be maintained in the baseline series for its good ability to detect corticosteroid sensitization. HIGHLIGHTS: We report a prevalence of budesonide contact sensitivity in Italy of 0.6%, confirming its decreasing trend. Late readings at day 7 permitted the diagnosis of contact allergy to budesonide in 37.8% of patients. A significant positive association with male gender, atopic dermatitis, and age > 40 years and a significant negative association with hand and face dermatitis was demonstrated by the MOAHLFA index.